Impact of integrating the concentrated solar power on the reliability of the Moroccan electricity system - Fahssi, Mohammed EL; Ouchbel, Taoufik; Zouggar, Smail; Elhafyani, Mohamed Larbi (International Journal of Electrical and Computer Engineering (IJECE), 2025)
In Morocco's electrical grid, the percentage of renewable energy used is rising. This growth can have significant impacts on the electrical system's ability to meet load because of unpredictable solar energy production. To evaluate the effects of concentrated solar power (CSP) generation and load evolution on the hierarchical level I (HLI: the capacity to cover the load on the premise of an endless node), this study is evaluating, by employing a Monte Carlo non-sequential simulation, decreasing the impacts on the ability and increasing the reliability of the Moroccan electrical grid. For that, we determine the CSP based on the hourly direct normal irradiation (DNI) for each site, the hourly conventional generation and the hourly load. Then we use these data as input elements in the Monte Carlo simulation to calculate the reliability indices like loss of load probability (LOLP), loss of load expectation (LOLE) and loss of energy expectation (LOEE).